Development of Multiplication and Division Concept Learning Media to Increase Student’s Problem Solving Skill and Learning Interest - Danuri Danuri; Taufik Muhtarom; Wahyu Wulandari; Padrul Jana (Universitas Ahmad Dahlan, 2020)
This study aims to (1) find out the quality of the learning media of dakon in mathematics subjects in class II-A of SD Muhammadiyah Ambarbinangun (2) determine the effectiveness of students learning using dakon media. The research method is research and development. The results of this study indicate that 1) The quality of learning media in terms of the review are a) the results of the assessment of media experts scored 65 with excellent criteria. Material experts score 36 with good criteria. b) the results of the student response questionnaire obtained a percentage of 93% with excellent criteria. 2) the learning process has been effectively reviewed from: a) the average results of student interest in learning by obtaining a percentage of 89% with outstanding criteria. b) the ability to solve problems, there are differences, as evidenced by the Paired Sample T-Test on the value obtained Sig. (2-tailed) 0,000 <0.05. The media of the dakon is effective in improving problem-solving skills and interest in learning, seen from the average score of 67.95 pretests and 83.28 post-test so that it can be concluded that the effective learning media.